Structural analyses of inositol phosphate second messengers bound to signaling effector proteins. - Blind, Raymond D. (Adv Biol Regul, 2019)
The higher-order inositol phosphate second messengers inositol tetrakisphosphate (IP4), inositol pentakisphosphate (IP5) and inositol hexakisphosphate (IP6) are important signaling molecules that regulate DNA-damage repair, cohesin dynamics, RNA-editing, retroviral assembly, nuclear transport, phosphorylation, acetylation, crotonylation, and ubiquitination. This functional diversity has made understanding how inositol polyphosphates regulate cellular processes challenging to dissect. However, some inositol phosphates have been unexpectedly found in X-ray crystal structures, occasionally revealing structural and mechanistic details of effector protein regulation before functional consequences have been described. This review highlights a sampling of crystal structures describing the interaction between inositol phosphates and protein effectors. This list includes the RNA editing enzyme “adenosine deaminase that acts on RNA 2” (ADAR2), the Pds5B regulator of cohesin dynamics, the class 1 histone deacetylases (HDACs) HDAC1 and HDAC3, and the PH domain of Bruton’s tyrosine kinase (Btk). One of the most important enzymes responsible for higher-order inositol phosphate synthesis is inositol polyphosphate multikinase (IPMK), which plays dual roles in both inositol and phosphoinositide signaling. Structures of phosphoinositide lipid binding proteins have also revealed new aspects of protein effector regulation, as mediated by the nuclear receptors Steroidogenic Factor-1 (SF-1, NR5A2) and Liver Receptor Homolog-1 (LRH-1, NR5A2). Together, these studies underscore the structural diversity in binding interactions between effector proteins and inositol phosphate small signaling molecules, and further support that detailed structural studies can lead to new biological discovery.